Analisis Pengaruh Faktor Usia, Pengalaman, Dan Pendidikan Terhadap Produktivitas Pekerja Proyek Terminal Bandara Sultan Hasanuddin - Serina Musa; Natsir Abduh; Savitri Prasandi Mulyani (Jurnal Penelitian Teknik Sipil Konsolidasi, 2026)
Indonesia, as a developing country, continues to carry out infrastructure development, including the expansion of Sultan Hasanuddin Airport's main terminal in Makassar. This research aims to identify the influence of age, experience, and education on worker productivity in the project. Using a quantitative approach, data was collected through direct observation, questionnaires, and interviews with relevant parties. The analysis showed that all three variables have a significant and positive impact on worker productivity. Work experience has the largest effect (0.393), followed by education (0.302) and age (0.270). These findings indicate that workers with higher experience and education tend to have better productivity, while age also contributes but with a smaller impact. This research underscores the importance of effective human resource management in supporting infrastructure development. By improving worker quality through education and experience, companies can achieve optimal results. The findings provide insights for project managers and policymakers in designing human resource